Molecular and phenotypic features for identification of the opportunistic pathogens Ochrobactrum spp - Teyssier, Corinne; Marchandin, Helene; Jean-Pierre, Helene; Diego, Isabelle; Darbas, Helene; Jeannot, Jean-Luc; Gouby, Anne; Jumas-Bilak, Estelle (Journal of medical microbiology, 2005)
1 Laboratoire de bactériologie, faculté de pharmacie, 15, avenue Charles Flahault, 34093 Montpellier Cedex 5, France 2 Laboratoire de bactériologie, hôpital Arnaud de Villeneuve, 34295 Montpellier Cedex 5, France 3 Laboratoire de bactériologie, hôpital Carremeau, 30060 îmes, France Correspondence Estelle Jumas-Bilak ebilakatuniv-montp1.fr Received April 10, 2005 Accepted July 6, 2005 Among the six species characterized within the genus Ochrobactrum , Ochrobactrum anthropi and Ochrobactrum intermedium are currently reported as opportunistic pathogens in humans. Since the species identification is mainly based on 16S rDNA analysis, the aim of this study was to search for other characteristics useful for Ochrobactrum species discrimination. Ribotyping, morphological and biochemical analyses, and antimicrobial susceptibility testing were performed for a panel of 35 clinical isolates, first identified to the species level using 16S rDNA sequencing. Type and reference strains of five Ochrobactrum species were comparatively analysed. Commercial identification systems such as API 20NE and VITEK 2 were tested for their ability to identify Ochrobactrum anthropi and to detect other members of the genus Ochrobactrum . An improved protocol for the identification of Ochrobactrum spp. by routine medical microbiology practices is proposed: isolation of a non-fastidious non-fermenting oxidase-positive Gram-negative rod resistant to all ß-lactams except imipenem indicates the genus Ochrobactrum , and the API 20NE system confirms the genus identification for most strains, whereas the VITEK 2 system using ID-GNB cards was less powerful. Urease activity, the mucoidy of the colonies, growth at 45 °C on tryptic soy agar, and susceptibility to colistin, tobramycin and netilmicin should be considered as differential characteristics for identification of O. anthropi and O. intermedium to the species level. However, definitive identification depends on genotyping methods. Abbreviations: AFLP, amplified fragment length polymorphism; DIG, digoxigenin. The GenBank/EMBL/DDBJ accession numbers for the 16s rDNA sequences reported in this paper are AF526518AF526526, AY917104AY917119 and AY918295AY918296.